Rumusan Delik dan Pemidanaan Bagi Tindak Pidana Pencemaran Nama Baik di Media Sosial - Erwin Asmadi (DE LEGA LATA: JURNAL ILMU HUKUM, 2021)
Social media currently plays a very important role in disseminating electronic information. Users as legal subjects are sometimes unaware of the words, memes or images that constitute electronic information which can adversely affect one's good name. Although disseminating information is a human right owned by every human being, but it is obliged to respect the rights of other citizens so that this form of punishment can be avoided. The presence of Law of the Republic of Indonesia Number 11 Year 2008 regarding Information and Electronic Transactions applies severe penalties for perpetrators who defame, namely a maximum imprisonment of 6 years. Therefore raises concerns about the disparity in its application so that the legal certainty is neglected, namely whether a person can be arrested or not even though his mistake is uncertain. This can occur due to the fulfillment of the requirements for detention in accordance with Article 21 paragraph (4) point a of the Indonesia Criminal Procedure Code. On the other hand, as part of human rights in the context of freedom of expression, it turns out that the conviction has changed and there is an authentic explanation or definition of the offense formulation in the Law of the Republic of Indonesia Number 19 of 2016.